2005
DOI: 10.1093/eurheartj/ehi496
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence between left ventricular 17 myocardial segments and coronary arteries

Abstract: The most specific segments (anterior, anteroseptal, and all apical segments except the infero-apical) correspond to LAD but no segment can be exclusively attributed to the RCA. Inferoseptal segments can be attributed to LAD or RCA, inferior and inferolateral segments to RCA or LCX, and mid-anterolateral segment to LAD or LCX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(73 citation statements)
references
References 31 publications
3
67
0
3
Order By: Relevance
“…The third finding was that area at risk revealed by CE-SSFP and T2-STIR (using the subset of scans that were of diagnostic value) was similar to the findings in previous studies of culprit artery distribution using myocardial perfusion scintigraphy. 18,19 The results provide evidence that CE-SSFP is an emerging alternative option for edema imaging. It is intriguing that a noninvasive multimodality CMR scan can be used to identify the location of the culprit artery, its perfusion territory, and the amount of residual myocardium amenable to salvage.…”
Section: Advances In Imaging Myocardial Salvagementioning
confidence: 80%
See 1 more Smart Citation
“…The third finding was that area at risk revealed by CE-SSFP and T2-STIR (using the subset of scans that were of diagnostic value) was similar to the findings in previous studies of culprit artery distribution using myocardial perfusion scintigraphy. 18,19 The results provide evidence that CE-SSFP is an emerging alternative option for edema imaging. It is intriguing that a noninvasive multimodality CMR scan can be used to identify the location of the culprit artery, its perfusion territory, and the amount of residual myocardium amenable to salvage.…”
Section: Advances In Imaging Myocardial Salvagementioning
confidence: 80%
“…Nordlund et al 17 also set out to compare their results with previous publications on identifying the culprit artery using single photon emission computed tomography. 18,19 The CMR image analyses were performed in a core laboratory using software designed by the same group in the University of Lund, Sweden. The CMR findings from assignment of the culprit artery territory were compared with the reference findings from the invasive coronary angiogram, taking into account the Rentrop collateral grade and infarct assessment using late gadolinium enhancement imaging with CMR.…”
Section: Relationship Between the Culprit Artery The Myocardial Areamentioning
confidence: 99%
“…It was presented with the remark that there is indeed tremendous variability in the coronary artery blood supply. The variation among patients was later verified in a clinical study that evaluated the correspondence between the 17 segments of the recommended model and the coronary arteries [19]. This great variability calls for using a patient-specific approach towards assessing the coronary arteries and their relation to the myocardium.…”
Section: Introductionmentioning
confidence: 91%
“…The Anderson-Wilkins acuteness score was developed to enable assessment of acuteness of myocardial ischemia from the 12-lead ECG, and studies have indicated that it may be associated with salvageable myocardium. 93,94 A recent study of 38 patients treated with primary PCI, in which SPECT and CMR imaging were used to determine AAR and final infarct size, showed a moderate correlation between the acuteness score and salvageable myocardium in patients with acute RCA occlusion but not in patients with LAD occlusion. At present, there is no clear consensus regarding the preferred ECG method to estimate AAR.…”
Section: 89 90mentioning
confidence: 99%